Expression of cell surface transmembrane carbonic anhydrase genes CA9 and CA12 in the human eye: overexpression of CA12 (CAXII) in glaucoma. Issue 4 (1st April 2003) - Liao, S-Y; Ivanov, S; Ivanova, A; Ghosh, S; Cote, M A; Keefe, K; Coca-Prados, M; Stanbridge, E J; Lerman, M I
Abstract : Purpose : Carbonic anhydrase enzymes (CAs) are universally involved in many fundamental physiological processes, including acid base regulation and fluid formation and movement. In glaucoma patients, CA inhibitors are very effective in lowering intraocular pressure by reducing the rate of aqueous humour secretion mediated by the CAs in the ciliary epithelium. In this work, we investigated the expression and tissue distribution of two recently discovered CA genes CA9 (CAIX) and CA12 (CAXII) in fetal, neonatal, and adult human eyes with and without glaucoma. Methods : CAIX and CAXII expression in 16 normal and 10 glaucomatous eyes, and in cultured non-pigmented ciliary epithelial cells (NPE) from normal and glaucoma eye donors was assessed by immunostaining. In addition, northern blot hybridisation was performed to assess expression of CA4, CA9, and CA12 mRNA in cultured NPE cells from normal and glaucoma donors. Results : CAXII was localised primarily to the NPE with its expression prominent during embryonic eye development but which decreased significantly in adults. CAIX expression in the NPE was very low. The epithelium of cornea and lens occasionally expressed both enzymes at low levels during development and in adult eye, and no expression was detected in the retina. The NPE from glaucoma eyes expressed higher levels of CAXII, but not CAIX, in comparison with normal eyes. This expression pattern was retained in cultured NPE cell lines. NPE cells from a glaucoma patient showed a five-fold increase in the CA12 mRNA level with no detectable expression of CA9 mRNA. Also, no expression of the CA4 gene encoding a GPI anchored plasma membrane protein was detected on these northern blots. Conclusions : Transmembrane CAIX and CAXII enzymes are expressed in the ciliary cells and, thus, may be involved in aqueous humour production. CA12 may be a targeted gene in glaucoma.